Registered nurses' experience of mentoring undergraduate nursing students in a rural context: a qualitative descriptive study. Issue 1 (2nd January 2019) - Bowen, Lynette; Kable, Ashley; Keatinge, Diana
Abstract : Background : Registered nurses in a rural context are expected to support undergraduate students during clinical placement, however, they may experience challenges that are unique to the rural context. Aim : To describe the registered nurses' experience of mentoring undergraduate nursing students on clinical placements in a rural context. Design : Qualitative descriptive study. Method: Data were collected from nine participants at two rural hospitals in Australia. Individual semi-structured interviews were conducted and content analysis was used to analyse data. Findings : Four categories emerged from the data: 'The challenges of mentoring', 'Supporting students and facilitating learning', 'Supporting registered nurses who mentor undergraduate nursing students' and 'The rewards of mentoring'. Conclusion : The experience of the rural registered nurse mentor is affected by limited staffing and skill mix, the generalist nature of their work, time constraints and lack of information about students. They need flexible strategies, improved communication and information about students attending clinical placements.